Ectoparasites of Chrysichthys Nigrodigitatus from Escravos Estuary, Delta State, Nigeria and its Zoonotic Implication on Fish Consumer - Eyo, Victor Oscar; Eriegha, Ochuko Eriegha; Amaka Michael; G. O. Nwabeze; D. C. Nwangwu; N. F. Aladetohun (Book of Proceedings for the 39th Annual National Conference (FISON) Abuja, 2024)
This study was conducted to evaluate the ectoparasites of C. nigrodigitatus from the Escravos Estuary, highlighting the public health implication on fish consumers within the area. A total of 180 Chrysichthys nigrodigitatus specimens were purchased from artisanal fishers in Okerenkoko community. The fish specimens were examined for ectoparasites at the Fisheries and Aquaculture Laboratory, Nigeria Maritime University, Okerenkoko. Results showed a low overall prevalence of 8.33%. The highest prevalence (2.78%) was recorded in monogenea (Gyrodactylus sp.) and least (2.22%) in protozoan cyst. Abundance and intensity were highest (0.10 and 4.50) in protozoan cyst and least in Dacytylogyrus sp. (0.04 and 1.33). Findings revealed that prevalence, abundance and intensity of ectoparasites in C. nigrodigitatus were higher (9.17%, 0.22 and 2.55) in rainy season than dry season. Size class of 40.00 - 49.90 cm recorded the highest prevalence, abundance and intensity (12.50%, 1.44 and 11.50) of ectoparasites. Female C. nigrodigitatus had a higher prevalence, abundance, and intensity of ectoparasites (8.87%, 0.23 and 2.55) compared to the males. In relation to organ, prevalence and abundance of parasites were highest (4.44% and 0.12) in the skin whereas intensity was highest (2.80) in the gills. In conclusion, the prevalence of ectoparasites in C. nigrodigitatus from the Escravos Estuary is low, indicating the healthy state of the estuary and the low risk of zoonosis among inhabitants of the estuary who consume C. nigrodigitatus. Therefore, to completely eliminate the risk of Zoonosis, hygienically prepared and properly cooked C. nigrodigitatus should be consumed.
Keywords: Ectoparasites; Chrysichthys nigrodigitatus; Zoonosis; Escravos Estuary; Prevalence; Intensity